Answer:
y = 2x - 10
Explanation:
Put the equation in the form y = mx + b where m is the slope and b is the y-intercept. (For example, y = 3x + 1 would have a slope of 3 and a y-intercept of 1)
First, find the slope by doing change in y divided by change in x:
6 - 8 / 8 - 9 = -2 / -1 = 2
This means the slope is 2 and the equation would be
y = 2x + b
Then, since you know (9, 8) is a solution, you can plug x = 9 and y = 8 into that equation
8 = 2 * 9 + b
8 = 18 + b
b = -10
The equation is y = 2x - 10